Iconoscopy Between Phaneroscopy and Semeiotic - De Tienne, André (Recherches sémiotiques / Semiotic Inquiry, 2013)
Phaneroscopy and semeiotic study two entities with distinct modes of being : the phaneron and the sign. Each consists in a continuum, one of first intention, the other of second intention, the latter lying within the former. Peirce sought to solve the question of the passage from one to the other since the time of his first publication ‘Upon a New List of Categories’. The mature writings reveal the important role the notion of image plays in this transition. Peirce indeed develops a pragmatic conception of image that turns the latter into the fundamental ingredient of the concrete experience of signs. An image in this sense is not a drawing or a picture, but at first a logical concept with a mathematical basis that helps explain the psychological phenomenon. The image is at the junction between the percept (phaneral element) and the perceptual judgment (the most elementary kind of semiotic event) through the percipuum, and it can be observed through a special kind of activity called iconoscopy. I shall present those properties of the image that allow it to govern the transition between phaneron and sign, and clarify in what sense Peirce could assert that images ‘instigate to judgment’.